Efektivitas Manajemen Risiko Dan Manajemen Proses Dalam Pencegahan Fraud di Divisi YAN HC PT. PLN UID Jatim - Al Abid, Muhammad Lailul Muzakky; Purwanto, Sugeng (Institut Agama Kristen Negeri Tarutung, 2024)
In today's era, we face various risks, such as fraud in various sectors, ranging from economic, social, political, environmental, business decisions and the insurance sector. The existence of this risk is closely related to how it is managed, which is an integral part of the organization both on a sectoral and universal scale. According to the report